Association of rs2070600 in advanced glycosylation end‐product specific receptor with prognosis of heart failure. (10th September 2020) - Li, Shiyang; Hu, Dong; Hu, Senlin; Sun, Yang; Zhang, Ying; Li, Huihui; Chen, Yanghui; Liu, Hao; Cui, Guanglin; Wang, Dao Wen
Abstract: Aims: Our objective was to investigate the association of common variants in the coding region of advanced glycosylation end‐product specific receptor (RAGE) and the prognosis of heart failure (HF). Methods and results: A total of 3394 HF patients were continuously enrolled from January 2009 to August 2018 with a median follow‐up of 20.4 months. Additionally, 2861 healthy subjects also participated in the study. By sequencing these two groups, we identified a common functional missense variant rs2070600 in the coding region of RAGE, which showed a significant association with the prognosis of HF [hazard ratio = 0.53, 95%, confidence interval (CI) = 0.30–0.94, P  = 0.03], but no association with the risk of HF (odds ratio = 0.52, 95%, CI = 0.66–1.04, P  = 0.106). A series of functional assays revealed that rs2070600‐A, but not ‐G allele, suppressed the expression of RAGE protein by facilitating the binding of miR‐125a‐3p. Furthermore, the RAGE messenger RNA levels of human peripheral blood lymphocytes were reduced in subjects with the rs2070600‐AA genotype compared with subjects with the rs2070600‐GG or ‐AG genotypes. Additionally, our Western blot results from human heart tissue showed increased RAGE expression in HF samples compared with that in healthy donors. Conclusions: Our results demonstrate that the common missense variant rs2070600‐A allele is associated with a reduced risk of cardiovascular death and cardiac transplantation by facilitating the binding of miR‐125a‐3p.